2000
DOI: 10.1677/joe.0.1650545
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in insulin-like growth factor binding protein-3 proteolysis and complex formation in the arthritic joint

Abstract: Increased concentrations of insulin-like growth factor (IGF) system components have previously been observed in rheumatoid arthritis (RA) and osteoarthritis (OA); however, disruption of the IGF axis and the implications for the disease process remain largely unaddressed. This study was undertaken to characterise the IGF binding protein (IGFBP)-3 proteolysis and complex formation systems in synovial fluid and to investigate changes in these systems in arthritic disease, and their impact on the availability of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 52 publications
3
18
0
Order By: Relevance
“…3 of this study and which has also been observed by other authors (Whellams et al 2000). In addition, in RA patients, the synovial fluid concentrations of IGFBP-3 were positively correlated with synovial fluid levels of interleukin-1 and tumour necrosis factor- (Neidel et al 1997).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…3 of this study and which has also been observed by other authors (Whellams et al 2000). In addition, in RA patients, the synovial fluid concentrations of IGFBP-3 were positively correlated with synovial fluid levels of interleukin-1 and tumour necrosis factor- (Neidel et al 1997).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, in the synovial fluid of patients with RA, the proteolysis of IGFBP-3 was decreased (Fernihough et al 1996, Whellams et al 2000 and the levels of IGFBP-3 were increased (Fernihough et al 1996, Tavera et al 1996, Whellams et al 2000. Inverse correlation between plasma IGFBP-3 levels and proteolysis of IGFBP-3 has also been found in patients after surgery, but show a reduction in circulating IGFBP-3 as a result of IGFBP-3-specific proteases (Davenport et al 1992).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, IGFBP can regulate the precise mechanism of action of IGF-I and -II (Kelley et al, 1996;Baxter, 2000;Jones and Clemmons, 1995). In human patients with RA and OA, a considerable increase in levels of IGF-I and -II are found in the SF compared with normal patients (Fernihough et al, 1996;Whellams et al, 2000). Levels of IGFBP-3 are also greatly enhanced together with a decrease in protease activity against this binding protein.…”
Section: Growth Factorsmentioning
confidence: 99%
“…Levels of IGFBP-3 are also greatly enhanced together with a decrease in protease activity against this binding protein. Thus, a molar excess of IGFBP-3 to IGF exists whereas the opposite is found in normal SF (Whellams et al, 2000). This implies that, despite having an increased level of IGF-I and -II, the growth factors are predominantly bound to high-affinity binding proteins and are unable to bind to their receptors.…”
Section: Growth Factorsmentioning
confidence: 99%
“…19 There are little quantified data on exact levels of these growth factors in disease but it is thought that increased exposure to serum and growth factors may occur due to a breach in vascular permeability and studies have shown increase in mRNA levels of growth factors with the assumption is that local pericellular concentrations are elevated. 20 Although not performed, measurements of synovial levels of IGF-1 and TGF-b 1 during isolation procedures may have assisted in determining baseline growth factor levels. In this study we confirmed serum and IGF-1 increased acid efflux in equine chondrocytes, albeit the concentration of IGF-1 required to produce this was higher than reported for other species (for example bovine, 10 ).…”
Section: Discussionmentioning
confidence: 99%